Impact of Web-Based Recruitment on Organizational Image and Organizational Familiarity: A Study among HR Professionals - Thawrani, Muhammad Ramzan (International Journal of Social and Management Studies, 2021)
Human Resource department is acknowledged as an essential department of contemporary organizations. Different activities are conducted by the HR department, out of which the function of recruitment holds great importance because it brings people into the organization. It is assessed that the companies of the private sector in Pakistan have well-equipped HR departments that utilize the latest technology in conducting different recruitment activities. With the adoption of the latest technological developments by private sector companies in the field of HR; this study is conducted to assess the impact of web-based recruitment on organizational image and organizational familiarity considering the mediating variables of quality of applicants and a wider range of candidates. In this study, the signaling and critical contact theory are tested. The sampling technique used in this study is purposive sampling. The sample size selected for this study is 220 with a response rate of 88%. The results of this research demonstrated that web-based recruitment has a positive effect on the organizational image and organizational familiarity. The results also suggested that web-based recruitment has a positive effect on mediating variables that are the quality of applicants and a wider range of candidates. Through this study, it is also assessed that the first mediating variable that is a wider range of applicants has a positive impact on the organizational image and organizational familiarity. Moreover, the second mediating variable that is quality of applicants has a positive impact on the organizational image but has no significant impact on organizational familiarity. Some of the results of this study are supported by the outcomes of previous studies and some are not supported because the past researches were conducted in different industries.